Experimentally Determined Material Parameters for Temperature Prediction of an Automobile Tire using Finite Element Analysis (R&D Journal, 2019)
The material parameters of an automotive truck tire were experimentally determined and validated for use in a thermal finite element analysis to determine the temperature distribution in the tire due to different operating conditions. Uni-axial tensile tests were performed on tire samples. The force displacement response of each was used to determine material properties by means of direct curve-fitting and iterative numerical procedures. Equivalent finite element simulation models were used to validate the properties. Hysteresis behaviour of the rubber regions were identified by dynamic mechanical analysis. Material definitions were incorporated into a finite element model to predict the steady-state heat generation and temperature distribution within a tire due to hysteresis. Experimental rolling tire temperature measurements were taken on a test bench. A comparison of the results with those obtained from the equivalent thermal models was used to validate the numerical models.